Local and non‐local elasto‐viscoplasticity in strain localization analysis of multiphase geomaterials. (23rd July 2015) - Lazari, M.; Sanavia, L.; Schrefler, B.A.; de Borst, R.; Borja, R. I.; Darve, F.; Pijaudier‐Cabot, G.; Whittle, A. J.
Summary In this paper, rate‐dependent plasticity is employed to regularize, for the scope of mesh independency, the numerical solution in strain localization process of multiphase geomaterials. Towards this goal, the viscoplastic Duvaut–Lions and the viscoplastic Perzyna models are implemented in an existing finite element code for multiphase porous media. Perzyna's model is then extended according to the non‐local approach, allowing for handling weakly rate‐sensitive materials for which viscoplasticity is not sufficient to meet numerical requirements. Assuming quasi‐static and isothermal conditions, the models are validated and applied in the numerical simulation of an undrained plane strain biaxial compression test on initially water‐saturated dense sand taken from the existing literature. An overview of the significant factors such as loading velocity and soil permeability in conjunction with viscosity on the formation of localization pattern is presented. The interaction of the two internal lengths introduced by non‐locality and viscosity is also discussed. Finally, the obtained results are analysed and compared emphasizing the capabilities and shortcomings of each regularization technique. Copyright © 2015 John Wiley & Sons, Ltd.